Methodology for NMPC Tuning with Takagi Sugeno Fuzzy Inference System and Multidimensional Fuzzy Sets for Applications in Non-linear Chemical Processes - J. A. Palacio Morales; J.A. Isaza Hurtado; A.F. Tobón Mejía; J.A. Herrera Cuartas (Revista Iberoamericana de Automática e Informática Industrial RIAI)
This paper presents a methodology for the tuning of the parameters of a nonlinear model based predictive controller (NMPC) based on an optimization technique, applied in the control of nonlinear chemical processes, with the purpose of facilitating the stage of determination of the adjustment values of this type of control strategies. The results allow to determine the performance of the NMPC tuned with the methodology proposed and validate the results with tunings developed through other strategies. The proposed methodology is applied to the control of the concentration of a reagent in a continuously stirred tank reactor (CSTR).